Group 15 pre-emergent herbicides differentially affect plant growth, cuticular wax composition, and fatty acid metabolism in blackgrass - Blyth, Hannah R.; Cornette, Laurent; Hunt, Barrie; Haslam, Richard P.; Beaudoin, Frédéric; MacGregor, Dana R. (Frontiers in Agronomy, 2025)
Pre-emergent herbicides are essential tools in weed management, yet for some, we lack a molecular-level understanding of how they work. Here, we investigated how three Group 15 pre-emergent herbicides - flufenacet, S-ethyl dipropylthiocarbamate (EPTC), and tri-allate - affected growth and biochemical responses of two blackgrass (Alopecurus myosuroides) biotypes. Using a sterile, agar-based system, we quantified early seedling growth across a range of herbicide concentrations. ED40 doses defined from these (60 nM for flufenacet on shoots, 90 mM for flufenacet on roots, 600 nM for EPTC, and 6 μM for tri-allate) were used to assess the herbicides’ effects on cuticular wax composition and fatty acid metabolism using two biotypes: herbicide-sensitive “Rothamsted”, and “Peldon” which has well-characterized metabolic herbicide resistance. Flufenacet and tri-allate were both less effective on Peldon. At the ED40 dose, EPTC was less effective on Rothamsted. Flufenacet inhibited both shoot and root growth. Tri-allate and EPTC inhibited shoot growth but had no significant effect on root growth. As expected for Group 15 herbicides, total shoot wax content was affected by EPTC (Peldon -32% and Rothamsted -20%), flufenacet (Peldon -13% and Rothamsted -48%) and tri-allate (Peldon -10% and Rothamsted -32%) as were many of the compounds with chain lengths ≥C26. Unexpectedly, many of the C14-C26 species measured were altered in tri-allate, e.g. shoot α-linolenic acid was reduced by 80% and 93% in Peldon and Rothamsted, respectively. Together, these results reveal Group 15 pre-emergent herbicides cause distinct, biotype- and organ-specific actions and suggest they have different target(s) in planta.